Success Factors in Improving Patients’ Adherence to Tuberculosis Treatment Program: Case Study in Sleman, Yogyakarta, Indonesia - Mario Yedi Mau; Titien Siwi Hartayu (Sanata Dharma University, 2023)
Improving patients’ adherence to treatment programs is important for the success of tuberculosis (TB) treatment. The study aims to identify the underlying factors of TB treatment program success. A qualitative approach, i.e., an in-depth interview, and the purposive sampling method in selecting respondents were used to conduct this study. There are 15 persons involved, i.e., 3 persons each: pharmacists as providers, TB programmers, medicines supervisor (MS), TB cadres as supporters, and recovered TB patients as actors (17 years old and over). The data obtained were analyzed using the triangulation method (providers, actors, and supporters). The results of the study show that the family's role is very important in MS by taking medicines from primary health care and giving medicines on time. TB counselors play a role in monitoring the treatment program and making occasional home visits to motivate patients to recover. TB programmers and pharmacists play a role in providing patients’ education and MS, as well as monitoring medication-taking schedules and medical check-ups. Patients play a role in motivating themselves to get back to work soon. In conclusion, the underlying factors in TB treatment program success are the discipline of providers, supervisors, supporters, and patients’ motivation.